Muscle contributions to mediolateral mass center acceleration during running - Hamner, S.; Seth, A.; Delp, S. (XXIIIth Congress of the International Society of Biomechanics, Jul 3-7 2011 in Brussels, Belgium, 2011)
The purpose of this study was to determine how muscles contribute to mediolateral acceleration of the body mass center over multiple strides during running at 3.96 m/s (6:46 min/mile). To achieve this, we developed and analyzed threedimensional muscle-actuated simulations of running that included 92 musculotendon actuators representing 76 muscles of the lower extremities and torso.